Burden movement in confined drift wall blasting tests studied at the LKAB Kiruna SLC mine - Wimmer, Matthias; Nordqvist, Anders A.; Ouchterlony, Finn; Nyberg, Ulf; Furtney, Jason (Luleå tekniska universitet, Geoteknologi, 2012)
Blasting in SLC (sublevel caving) takes place in a semi-confined situation. Blasted material swells while the caved material compacts, and also, to a lesser extent, fills parts of the void volume of the production drift. Several analytical and empirical models have been developed in the past. However, understanding of the interaction of semi-confined blasting conditions, SLC blast design and rock mass characteristics on rock breaking performance is rudimentary. Instrumentation of the blasted burden with various sensors and study of the dynamics of burden movement against confinement is therefore important. Such measurements are very scarce and thus different systems have been tested both in laboratory and in the field. Main focus was thereby the development of measuring equipment that could be scaled up to full-scale SLC blasting and installed behind the rings. In the field tests, blastholes were drilled in a pillar, parallel to a cross cut drift in the LKAB Kiruna SLC mine. The burden constraint was achieved either by filling the drift of 7.0 x 5.2 m (width x height) with rock masses or reinforcing the drift wall. The tests were instrumented with different redundant sensors, which were installed in holes drilled from a parallel cross cut. The most promising one was a concept, which combines the initial movement recorded by an accelerometer designed to minimize zero-shift with the final displacement recorded by a fibre photoelectric sensor (‘fibre-optic zebra gauge’). For the filled drift wall blasting test the maximum velocity varied between 16 - 32 m/s with a compaction in the range of 4 - 5 %. A gap was verified to exist between the intact pillar and the blasted material. By comparison, the velocity for the unconfined situation yielded a considerably increased velocity (42 - 47 m/s). In addition, ‘Blo-Up’, a component within the Hybrid Stress Blast Model (HSBM), was used to model the blasting results. The ob-jective was to show that reasonable predictions of fragmentation and burden movement under confined ...